2014
DOI: 10.1021/am500576p
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Magnetic Porous Carbon Microspheres for Removal of Methylene Blue by a Heterogeneous Fenton Reaction

Abstract: High-specific-surface-area magnetic porous carbon microspheres (MPCMSs) were fabricated by annealing Fe(2+)-treated porous polystyrene (PS) microspheres, which were prepared using a two-step seed emulsion polymerization process. The resulting porous microspheres were then sulfonated, and Fe(2+) was loaded by ion exchange, followed by annealing at 250 °C for 1 h under an ambient atmosphere to obtain the PS-250 composite. The MPCMS-500 and MPCMS-800 composites were obtained by annealing PS-250 at 500 and 800 °C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
134
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(139 citation statements)
references
References 53 publications
5
134
0
Order By: Relevance
“…6), the relatively strong reflection peaks at 2h = 30.0°, 35.5°, 43.2°, 53.8°, 57.2°, and 62.6°were ascribed to the (2 2 0), (3 1 1), (4 0 0), (4 2 2), (5 1 1), and (4 4 0) planes, which was in good agreement with the database of magnetite (JCPDS 65-3107). These data indicated that the Fe 3 O 4 had been successfully coated with SiO 2 and RF shells, resulting in a highly crystalline cubic spinel structure [37,38]. In Fig.…”
Section: Morphology and Structure Characterizationmentioning
confidence: 77%
See 1 more Smart Citation
“…6), the relatively strong reflection peaks at 2h = 30.0°, 35.5°, 43.2°, 53.8°, 57.2°, and 62.6°were ascribed to the (2 2 0), (3 1 1), (4 0 0), (4 2 2), (5 1 1), and (4 4 0) planes, which was in good agreement with the database of magnetite (JCPDS 65-3107). These data indicated that the Fe 3 O 4 had been successfully coated with SiO 2 and RF shells, resulting in a highly crystalline cubic spinel structure [37,38]. In Fig.…”
Section: Morphology and Structure Characterizationmentioning
confidence: 77%
“…It also produces iron sludge as a byproduct of the treatment, which is an additional environmental contaminant [62]. Fe 3 O 4 nanospheres are an ideal heterogeneous Fenton catalyst due to the existence of Fe 2+ [38,63,64]. This material is free from some of the disadvantages of homogeneity mentioned above, and its magnetic capabilities offer the additional advantage of making it easier to separate from the reaction mixture via an external magnetic field.…”
Section: Catalytic Properties Of Magnetic Rattle-type Carbon Spheresmentioning
confidence: 99%
“…Magnetic porous carbons have been already prepared and suggested for a number of adsorption applications in the liquid phase [61][62][63]. Iron-containing activated carbons can indeed be more easily recovered out of the effluents after some targeted pollutants are removed.…”
Section: Iron/carbon Hybrid Materialsmentioning
confidence: 99%
“…are very interesting for the investigation of magnetic properties and applications [27,[58][59][60].…”
Section: A N U S C R I P Tmentioning
confidence: 99%